Does the Growth in Non-Banking Financial Institutions Signal the Death of a Bank as a Brand: A View from the South African Banking Market? - Nyoka, Charles (Acta Universitatis Danubius. Œconomica, 2022)
The banking sector has undergone considerable changes since the Global Financial Crisis (GFC) as the countries no longer operate in isolation, owing to globalization (Viegi, 2008). Yesteryear, banks were easily recognizable as a brand. Today brand bank is wanning, and profit margins are being squeezed. In the contest of South African Banking market this paper investigates whether the emergency of Non-Banking Financial Institutions is threatening the brand of a bank. Using a guided questioner, this paper asserts that the emergency of Non-banking institutions has eroded the banks’ brand and has impacted on patronage and loyalties to traditional models of banking. Based on Cronbach’s alpha criterion, results from the study reveal that the survey instrument used to collect data from participants was statistically reliable. Overall, results on frequency statistics and factor loadings computed based on the exploratory factor analysis technique reveal that respondents largely concurred with the assertion that brand bank is on its way to the grave due to the emergence and growth in non-banking financial institutions in South African banking market. The results will benefit banks ‘s efforts in re-aligning their products with market trends and assist policy makers and regulatory authorities in tracking banking practices in their economies